Excess brain protein oxidation and enzyme dysfunction in normal aging and in Alzheimer disease. - Smith, C D (1991)
The relationship between Alzheimer disease (AD) and aging is not currently known. In this study, postmortem frontal- and occipital-pole brain samples were obtained from 16 subjects with AD, 8 age-matched controls, and 5 young controls. These samples were analyzed both for protein oxidation products (carbonyl) and the activities of two enzymes vulnerable to mixed-function oxidation, glutamine synthetase and creatine kinase. Glutamine synthetase is more sensitive to mixed-function oxidation than creatine kinase. Carbonyl content rises exponentially with age, at double the rate in the frontal pole compared with the occipital pole. Compared with young controls, both aged groups (AD and age-matched controls) have increased carbonyl content and decreased glutamine synthetase and creatine kinase activities, which are more marked in the frontal than occipital pole in all instances. We conclude that protein oxidation products accumulate in the brain and that oxidation-vulnerable enzyme activities decrease with aging in the same regional pattern (frontal more affected than occipital). However, only glutamine synthetase activity distinguishes AD from age-matched controls: Because glutamine synthetase activity is differentially reduced in the frontal pole in AD, we suggest that AD may represent a specific brain vulnerability to age-related oxidation.